Choosing Objective and Non-objective Test as Instrument for Assessment of EFL Student Learning Outcomes - Fitria, Tira Nur (Globish: An English-Indonesian Journal for English, Education, and Culture, 2024)
This research describes the type of questions both objective and non-objective tests, benefits, and weaknesses of EFL students’ learning outcomes. This research is a descriptive qualitative. The analysis shows that the written test can be used as a measuring instrument for knowing students’ abilities. The form of the written test consists of objective and non-objective. An objective test consists of multiple potential answers or responses for students to choose one including completion, multiple-choice, matching, short answer, and true-false test. Non-objective tests consist of essays/descriptions for students to compose or organize answers in their language including an essay in limited/restricted essay and free essay tests. Teachers/lecturers should consider aspects of making the tests. They have differences in measured learning outcomes, preparation of question items, sampling of learning materials, control of student answers, scoring, influence on the learning process, and reliability. However, both objective and non-objective tests also have several advantages and disadvantages.